Structural microhabitat use by endemic cyprinids in a Mediterranean‐type river: Implications for restoration practices. Issue 1 (12th October 2017) - Santos, José Maria; Rivaes, Rui; Boavida, Isabel; Branco, Paulo
Abstract: Endemic freshwater fish from the Mediterranean region are among the most threatened species in the world owing to increasing river degradation. Because of such threats, the number of river restoration projects has greatly increased. However, they are seldom planned with consideration of the species' life history, often resulting in erroneous practices that compromise their success. This study assessed the seasonal and size‐related microhabitat use by three endemic cyprinids (Iberian barbel, Lucio barbus bocagei ; Iberian straight‐mouth nase, Pseudo chondrostoma polylepis ; and calandino, Squalius alburnoides ) using a modified point electrofishing procedure in a Mediterranean river. A multivariate approach was then employed to analyse both structural resource use and availability data. All species showed non‐random microhabitat use. The barbel and nase shifted to faster‐flowing positions (>25 cm s −1 ) with a coarser substratum (>150 mm particle size) during spring and to sheltered positions (50–100% instream cover) during autumn. Calandino selected more covered areas in autumn (>60% cover) and shifted to shallower positions from this season (>40 cm) to summer (<35 cm). Significant size‐related differences in microhabitat use were consistent for the three species, with smaller individuals occupying on average shallower microhabitats. Significant resource‐use overlap between species size classes increased from autumn to summer, occurring mainly between juvenile and small adult barbel and calandino. The present study helped develop recommendations for river restoration practices that may have a wider application, particularly for other Mediterranean‐type rivers. Cover was found to be critical for all species, in particular for calandino, which could be classified as a shelter‐oriented eurytopic species. Restoration scenarios should therefore consider maintaining cover habitats during unfavourable flow conditions for these species. Lithophilic spawners, which were highly responsive to velocity and substratum, could particularly benefit from the creation of gravel bedforms and artificial riffles to enhance depth and flow variability.